A Case of COVID-19 Presenting as Acute Liver Failure - Nawghare, Pankaj; Nair, Sujit; Jain, Shubham; Bansal, Saurabh; Chandnani, Sanjay; Rathi, Surbhi; Rathi, Pravin (Scripta Medica, 2022)
Although children with COVID-19 make up a small proportion of patients and have milder symptoms than adults, liver damage is a well-documented side effect of COVID-19 infection. Most liver damage caused by COVID-19 is modest. In this report, a case of a 6-year-old child who was hospitalised to a paediatric intensive care unit (PICU) with COVID-19 manifested as acute liver failure is described.